Understanding of Physics Concepts by Samudra Langsa University Students - Husna, Nuril; Evendi, Evendi; Safitri, Rini; Wahyuni, Wahyuni (Universitas Malikussaleh, 2021)
Understanding is the main basis for self-improvement in using various methods to create ideas. There are several levels in understanding, namely cognitive primitive, Image Making, Image Having, Property Noticing, formalizing, observing, structuring, inventizing c. This research is a type of research with a descriptive qualitative approach. The results showed that the first subject had the ability to understand concepts and was in the formalizing stage. There are as many as 35% of students who are at the formalizing stage. The second subject is still in the image-making stage. As many as 65% of students are in the image-making stage.